Faktor-Faktor yang Mempengaruhi Kinerja Reksadana Syariah di Indonesia dan Malaysia - Muhammad, Rifqi; Arifah, Imtinani; Nugraheni, Peni (Fakultas Ekonomi Universitas Samudra, 2021)
The study aims to examine the effect of operational performance, age, and size of mutual fund, on the performance of Islamic mutual funds in Indonesia and Malaysia. The data used collected from the monthly reports of Islamic mutual funds for the period 2016-2018, and then analyzed using panel data regression method. The total number of data was 44 from Indonesia and 46 from Malaysia. The results of statistical tests show that the operational performance and size of Islamic mutual funds have no effect on the performance of Islamic mutual funds both in Indonesia and in Malaysia. Meanwhile, the age of mutual funds is proven to have a significant negative effect on the performance of Islamic mutual funds in Indonesia, but on the contrary it is identified as having a significant positive effect on the performance of Islamic mutual funds in Malaysia. Furthermore, this study did not find any significant differences between the performance of Islamic mutual funds in Indonesia and Malaysia